Using gum arabic тo form oil-water emulsions in food products - Луговська, Оксана Андріївна; Сидор, Василь Михайлович; Нікітчіна, Тетяна Іванівна (Eastern-European Journal of Enterprise Technologies, 2014)
Despite the large number of studies on using gum arabic in various fields of the food industry, little attention has been paid to the study of this stabilizer in food emulsions for beverages. In this paper, the influence of the physical and chemical properties of gum arabic when using it in food products was determined. Using the dependence theory of the emulsion stability on the ratio of water gum arabic stabilizer and the oil phase, the process of obtaining pre-emulsion and the homogenization mode of the emulsion system, the formulations of food emulsions with varied amount of stabilizers and the fat phase were developed. The results of the samples of food emulsions using different amounts of gum arabic (at the constant oil phase) and the samples of emulsions with the variable oil phase and a constant amount of gum arabic were considered in detail. The analysis of the prepared emulsion indicators, such as the measured particle size, viscosity, turbidity and dependence on the ratio of water and oil phases of the system, the process parameters, was carried out. The indicators of each emulsion were measured: viscosity by the Brookfield viscometer, particle size by a microscope EASTCOLIGHT 92012-ES (100x, 250x, 550x, 750x) , turbidity by a turbidimeter 2100P. The optimal ratio between water stabilizer and oil phase of the emulsion, which is characterized by obtaining the maximum amount of emulsion particles of up to 1 micron was determined. Emulsion has a highly reliable stability if the particle size is less than 1 micron and has some turbidity, but the more particles are smaller than 1 micron, the less turbidity is. If there is insufficient amount of stabilizer, a small number of particles larger than 1 micron is formed, leading to the appearance of “oil ring” during long-term storage. The results can form the basis for the establishment of production technology for beverage emulsions as a class of food products. Creating a stable emulsion system is a relevant issue in the food industry, that is why the studies are useful and important for the development of new food products.